Potential of bacterial chitinolytic, Stenotrophomonas maltophilia, in biological control of termites - Faiza Jabeen; Ali Hussain; Maleeha Manzoor; Tahira Younis; Azhar Rasul; Javed Iqbal Qazi (Egyptian Journal of Biological Pest Control, 2018)
Abstract Termites are important pest of crops, trees, and household wooden installments. Two species Coptotermes heimi and Heterotermes indicola are the major species of termites that results in great economic loss in Asia including Pakistan. Chitinases have drawn interest because of their relevance as biological control of pests. The study was performed to screen chitinolytic bacteria from dead termites and to determine their chitinolytic activity in degrading chitin content of termites. Ten isolates were obtained forming clear zones on chitin-containing agar plates. One isolate (JF66) had the highest (3.3 mm) chitinolytic index. Based on sequence of 16S rRNA gene, the isolate was identified as Stenotrophomonas maltophilia with (99%) similarity under Accession number KC849451 (JF66), and DNA G + C content was found to be (54.17%). S. maltophilia (JF66) produces chitinases upto 1757.41 U/ml at 30 °C and pH 6.0 employing diammonium phosphate as a nitrogen source. Chitinase gene was also extracted and gets sequenced that confirmed its presence. Whole culture and different concentrations of crude enzyme of the isolate were tested on the chitin covering of termites. Mortalities showed that crude enzyme of isolate could degrade chitin of both species of the termites C. heimi and H. indicola. Chitinase produced by S. maltophilia had potential application as biocontrol agent for termites, but it is assumed that purification of chitinases may produce more prominent results.